Iraq Crude Oil Exports – April, May, and June/ 2024 - SOMO, Oil Marketing Company (Journal of Petroleum Research and Studies, 2025)
Table 1. Iraq Crude Oil Exports – April 2024 Table 2. Iraq Crude Oil Exports – May 2024 Table 3. Iraq Crude Oil Exports – June 2024